2021
DOI: 10.1088/1361-6439/ac0516
|View full text |Cite
|
Sign up to set email alerts
|

Removal of recast layer in the laser drilled film cooling holes by a two-step inner streaming electrochemical technique

Abstract: High-power millisecond laser is an efficient tool to manufacture micro holes, but the laser induced thermal defects, such as recast layer (RL), micro cracks and heat affected zone, are difficult to avoid. However, some important components, like turbine blades, are very sensitive to these defects, therefore, they must be eliminated in the manufacturing process of film cooling holes. We propose a combined processing method which includes high-power laser pre-drilling and electrochemical post-processing. One nov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…However, laser processing is a high-speed thermal shock process, with high density heat rapidly concentrated in a small processing range, resulting in local temperature of up to tens of thousands of degrees Celsius within a very short time, which leads to material gasification and melting, thereby producing a large amount of molten material. If the molten material cannot be completely eliminated, it will be cooled and re-solidified around the processing path to form a recast layer [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…However, laser processing is a high-speed thermal shock process, with high density heat rapidly concentrated in a small processing range, resulting in local temperature of up to tens of thousands of degrees Celsius within a very short time, which leads to material gasification and melting, thereby producing a large amount of molten material. If the molten material cannot be completely eliminated, it will be cooled and re-solidified around the processing path to form a recast layer [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, compared with laser processing, results showed that there was no sputtering on the surface of the material processed by LECM, and there was no recast layer on the side wall of the micro holes. Duan et al [15] found that laser processing in oxidation-assisted gases may generate an oxide insulating layer, the subsequent electrochemical corrosion could not preferentially dissolve the recast layer. Using non-oxidation-assisted gases, an ideal hole shape with smooth sidewalls can be obtained, and the inner surface was smoother.…”
Section: Introductionmentioning
confidence: 99%